W gąszczu filozoficznych rozróżnień. Pawła Rojka systematyzacja podstawowych zagadnień dotyczących tropów i uniwersaliów - Luc, Joanna (Filozofia Nauki, 2020)
This paper reviews Paweł Rojek’s book Tropy i uniwersalia: Badania ontologiczne (Tropes and Universals: Ontological Investigations). The subject of the book are the titular notions of tropes (i.e., abstract particulars) and universals. The first three chapters contain conceptual clarifications and the remaining three chapters are devoted to the interpretation of particular philosophers (Roman Ingarden, Thomas Aquinas, Hegel, and George Frederick Stout) in the light of the previously introduced distinctions. The review summarizes each chapter and discusses some objections to the author’s theses.